Religious Moderation Education Model for Non-Muslim ‎Students Through Interfaith Internships at Pesantren - Yusuf, Achmad; Makhzuniyah, Minhah (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study explores the Religious Moderation Education Model for ‎Non-Muslim students in Islamic boarding schools, aiming to ‎understand the process of internalizing religious moderation attitudes ‎and analyze students' attitudes towards them. Using the case study ‎method, the results show that this approach helps Non-Muslim ‎students internalize the values of tolerance and mutual respect. The ‎attitude of student moderation also contributes to integration and ‎harmony between students. Social interaction, daily routines, tafsir ‎recitation, and open dialogue in the dormitory reinforce an inclusive ‎and tolerant attitude towards religious differences. This research ‎emphasizes the importance of moderate education in creating an ‎inclusive learning environment, which contributes to the development ‎of a harmonious and tolerant society. In conclusion, the Religious ‎Moderation Education Model in Islamic boarding schools has proven ‎to be effective in forming an attitude of tolerance and interfaith ‎understanding